Variation in diet of desert bighorn sheep (Ovis canadensis nelsoni): Tradeoffs associated with parturition - Blum, Marcus E.; Stewart, Kelley M.; Cox, Mike; Shoemaker, Kevin T.; Bennett, Joe R.; Sullivan, Benjamin W.; Wakeling, Brian F.; Bleich, Vernon C. (Frontiers in Ecology and Evolution, 2023)
We studied diet quality and forage selection by bighorn sheep before and following parturition to determine how nutritional demands associated with rearing offspring influenced forage acquisition. Selection of forage and habitats is driven by nutritional needs of individuals. Some species may sacrifice nutritional quality of forage for the mother in favor of safety of offspring (risk-averse strategy), immediately following parturition. We used desert bighorn sheep, Ovis canadensis nelsoni, to investigate that potential tradeoff. We captured and radio-collared female bighorn sheep from 2016 to 2018. We used vaginal implant transmitters (VIT)s in pregnant females to identify parturition and to capture and radio-collar neonates to monitor survival of young. We collected fecal samples throughout the breeding season and throughout the year to understand diet quality and composition throughout those temporal periods. We determined diet quality and composition for pre-parturient females, females provisioning offspring, females that lost offspring, and non-pregnant individuals using fecal nitrogen and DNA metabarcoding analyses. Additionally, we compared the diet quality and composition of offspring and adult females during the spring, as well as summer and winter months. Our results indicated differences in diet quality between individuals provisioning offspring and those whose offspring had died. Females that were provisioning dependent young had lower quality diets than those that lost their offspring. Diet composition among those groups was also markedly different; females that had lost an offspring had a more diverse diet than did females with dependent young. Diet quality differed among seasons, wherein offspring and adult females had higher quality diets during the spring months, with decreasing quality as the year progressed. Diet diversity was similar across seasons, although spring months tended to be most diverse. Our results support tradeoffs associated with risk-averse strategies made by adult females associated with parturition. Nutritional quality of forage was linked to provisioning status, indicating that females were trading diet quality for safety of offspring, but those females whose offspring had died selected high quality forages. Those results help explain habitat selection observed in mountain ungulates around parturition and provide further insight into the evolutionary processes and adaptive significance exhibited by those specialized artiodactyls.